A new species of Bidessus from Anjozorobe-Angavo and a review of Malagasy Bidessus (Coleoptera, Dytiscidae) - Bergsten, Johannes; Ranarilalatiana, Tolotra; Biström, Olof (European Journal of Taxonomy, 2020)
We review the species of Bidessus of Madagascar and describe Bidessus anjozorobe sp. nov. from material collected in Anjozorobe forest. Anjozorobe is part of the Anjozorobe-Angavo Protected Area, which is an important corridor of transition forest between typical eastern humid forests and the residual sub-humid forest of the Central Highlands. Bidessus longistriga Régimbart, 1895 and Bidessus perexiguus Kolbe, 1883 are widespread but endemic low-altitude species on Madagascar. Bidessus nesioticus Guignot, 1956 is an alpine species described from near the peak of the Ankaratra mountain massifs at 2500 m a.s.l. We recollected the species for the first time since its description, in Ankaratra and in a new area above 2000 m a.s.l. in the Andringitra mountain further south. Bidessus cf. nero Gschwendtner, 1933 is tentatively recorded for Madagascar for the first time but further studies are needed to test the status of mainland and insular populations. Bidessus apicidens Biström & Sanfilippo, 1986 has not been recollected on Madagascar since 1970. All species are endemic to Madagascar except potentially Bidessus cf. ceratus and Bidessus cf. nero described from Uganda and the Democratic Republic of the Congo, respectively. The older records of the two non-endemic species Bidessus complicatus Sharp, 1904 and Bidessus ovoideus Régimbart, 1895 on Madagascar could not be verified.